The productivity of European banking sector: A review of the post-2000 literature - Dario Maradin; Zdenko Prohaska; Stella Suljic Nikolaj (UTMS Journal of Economics, 2019)
Numerous bank productivity studies indicate rapid changes in the structure of the financial services industry and advances in financial and nonfinancial technologies. Based on the literature review, this paper analyses the theoretical background of two concepts of performance evaluation - the terms efficiency and productivity, and empirically, the performance evaluation of banks, i.e., the measurement of the productivity and research results of previous authors' studies of the European banking sector applying different scientific methods. Nonparametric or parametric techniques, such as DEA with the Malmquist total factor productivity index or SFA method, are increasingly being used to evaluate the productivity of banks and other financial institutions. The measurement of bank productivity is of vital importance from both a microeconomic and a macroeconomic point of view. Therefore, the purpose of this paper is to present productivity literature review of the most relevant studies of the European banking sector published after year 2000. The main results of this research will be the comparative analysis of different empirical scientific studies regarding banking sector productivity evaluation.
Keywords: G21; G34; D24; C61; 330; performance evaluation; productivity growth; efficiency; banks; Malmquist productivity index